2018
DOI: 10.1111/jeb.13229
|View full text |Cite
|
Sign up to set email alerts
|

Can Ebola virus evolve to be less virulent in humans?

Abstract: Understanding Ebola virus (EBOV) virulence evolution not only is timely but also raises specific questions because it causes one of the most virulent human infections and it is capable of transmission after the death of its host. Using a compartmental epidemiological model that captures three transmission routes (by regular contact, via dead bodies and by sexual contact), we infer the evolutionary dynamics of case fatality ratio on the scale of an outbreak and in the long term. Our major finding is that the vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…This increased virulence is attributable to viral evolution, as experiments in in vitro and animal systems suggested that the coordinated expression of eight genes unique to the 1918 virus was responsible for the increased lethality [35,36]. For other human pathogens, such as smallpox, virulence fluctuated wildly from one wave to the next [37,38], with the high-virulence ("variola major") strains showing functional differences from the low virulence ("variola minor") strains [39,40] in in vitro and animal studies. The instability of smallpox virulence over time contradicts the notion of obligatory viral attenuation and may foreshadow similar behavior during the current pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This increased virulence is attributable to viral evolution, as experiments in in vitro and animal systems suggested that the coordinated expression of eight genes unique to the 1918 virus was responsible for the increased lethality [35,36]. For other human pathogens, such as smallpox, virulence fluctuated wildly from one wave to the next [37,38], with the high-virulence ("variola major") strains showing functional differences from the low virulence ("variola minor") strains [39,40] in in vitro and animal studies. The instability of smallpox virulence over time contradicts the notion of obligatory viral attenuation and may foreshadow similar behavior during the current pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, our modelling result is scale-free and applies to any size of mosquito population, or any spatial range. Moreover, our reproduction number represents solely the lower bound of the true basic reproduction number, as the model does not account for any other transmission route - namely horizontal, from mammal hosts to mosquitoes, and vertical, from female mosquitoes to eggs [41].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a spyware cyber attack, which aims to maximize the amount of data siphoned from a computer over an extended period of time, (where fitness might be measured as the volume of leaked data) would not accurately be compared to Ebola virus. Ebola virus maximizes its total transmission by destroying its host quickly via hemorrhaging [35]. Such fast and obvious harm would undermine the intent of spyware, which cannot continue to gather data from an incapacitated computer.…”
Section: Framing the Context Of Defensementioning
confidence: 99%